Nipah Virus (NiV) Infection: Is Nepal Prepared for the Possible Outbreak? - Shrestha, Dhiraj; Bhattachan, Balkrishna (Nepal Journal of Biotechnology, 2019)
After 20 years of the first Nipah Virus (NiV) outbreak in the world, it re-emerged as the outbreak in India. WHO has recognized NiV as a potent epidemic threat to human health. Both animal-to-human and human-to-human transmission of zoonotic NiV has been documented. Fruit bat of Pteropodidae family is the natural reservoir of the virus. Thus, the territorial habitat of these bats is the high risk zone of NiV outbreak. The symptoms are very nonspecific and the pathogenicity of NiV is yet to be fully understood. Diagnosis of NiV infection still relies on molecular techniques. Till date, no drugs or vaccines against NiV has been approved. Some research have presented arrays of the possible treatment and prevention option, but without sure shot implications. So, appropriate precautions are the only currently available prevention option. Nepal is yet to experience a NiV outbreak but that does not undermine the risk posed to the general population. High risk countries including Nepal should be well prepared to tackle the possible outbreak in future.